Memory and the Power of Remembrance of the Character Ali in the Novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna - Adella Hilda Sri Januarti Januarti; M. Helmi; Sakrim (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe the memories and recall of the character Ale in the novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna using a literary psychology approach based on Ludwig Klages’s personality theory. The study was conducted in 2026, with the research subject being the novel Seporsi Mie Ayam Sebelum by Brian Khrisna, published by Grasindo in 2025. This study employs a qualitative descriptive method with data collection techniques consisting of reading and note-taking. The research data consists of quotations of sentences, dialogues, and narratives related to the aspects of memory and the ability to recall of the character Ale. The research instrument consists of data cards, while the data analysis technique was carried out through the stages of classification, description, and interpretation based on Ludwig Klages’ theory. The results of the study indicate that the character Ale’s memory encompasses the ability to recall past experiences, remember behavioral habits, harbor expectations regarding future impressions, revisit erroneous impressions resulting from traumatic experiences, and engage in fantasy as a form of psychological escape. Meanwhile, the character Ale’s memory capacity is divided into two forms: the capacity to recall experiences or events, and the capacity to recall objects that evoke the character’s emotional experiences. This study demonstrates that past experiences stored in memory have a significant influence on the development of the psychological state and personality of the character Ale in the novel.